UXUC - User experience & urban creativity scientific journal, vol.1, nº2 (Dez. 2019) - Neves, Pedro Soares (2021)
As travelers come and go worldwide, many leave marks in a silent exchange, communicating that I was here, I exist. They embrace and taunt each other over time and distance, sharing in-jokes, and making rude gestures against surveillance and control. Marks about seeking community, personal bests, creating a customized, personalized experience of neighborhoods. This is ours. You are welcome. Some people and some experiences are still free. Unsurprisingly, some graffiti and experience design professionals connect, emerge, cross over, and enhance the many disciplines in each. Artists bring graffiti writing and design skills to the digital, sculptural, and architectural worlds. Experience designers document, facilitate, and embrace graffiti culture and experience in their own lives and work, recognizing the importance of people owning, co-creating, and humanizing the artifacts and environments we share. With this journal, we hope to illuminate some of the compelling work being done at these intersections of people, concerns, design, research, media, environments, liberty, trespass, and aesthetics.